Methods to Evaluate Skin Penetration In Vitro - Stella Zsikó; Erzsébet Csányi; Anita Kovács; Mária Budai-Szűcs; Attila Gácsi; Szilvia Berkó (MDPI AG, 2019)
Dermal and transdermal drug therapy is increasing in importance nowadays in drug development. To completely utilize the potential of this administration route, it is necessary to optimize the drug release and skin penetration measurements. This review covers the most well-known and up-to-date methods for evaluating the cutaneous penetration of drugs in vitro as a supporting tool for pharmaceutical research scientists in the early stage of drug development. The aim of this article is to present various experimental models used in dermal/transdermal research and summarize the novel knowledge about the main in vitro methods available to study skin penetration. These techniques are: Diffusion cell, skin-PAMPA, tape stripping, two-photon microscopy, confocal laser scanning microscopy, and confocal Raman microscopic method.